Estudio de la calidad de suelos agrícolas de fincas productoras de ciclo corto en la zona de Babahoyo - Mora Guerrero, Clara Julisa (2021)
Ecuador is characterized by the great variety and richness of its natural resources, among which the presence of volcanic soils with high agricultural potential and a wide range of climates over short distances can be highlighted. Very early, man knew how to take advantage of these favorable conditions and develop a flourishing agriculture that is distinguished by its productions of a remarkable diversity where tropical and temperate climate products alternate. The organic matter content in farm soils is low and affects aggregate stability, nutrient retention, water availability, erosion reduction, and increased activity of microorganisms. It is necessary to increase its content, taking into account the origin of the material and the amount available in the soil. The K, P and NO3 dose should be increased, the Ca and Mg dose should be lowered, in micronutrients the low dose of Mn and Fe should be raised, applying soluble fertilizers with a source of Zn and B, although the modification of the pH will make these elements more available. If the irrigation system does not allow to attend to exclusive cases, applications to the soil or foliar route are recommended in case of micronutrients. The current soil quality index on average is 39.8, which can be improved by 34.3%, implementing deep subsoiling practices, reducing water pressure, adding organic matter, correcting pH and nutritional antagonisms.